Wykorzystanie metod eksploracyjnej analizy tekstu do identyfikacji zmienności koncepcji zawartych w dużych zbiorach publikacji naukowych - Grabowski, Mariusz (The Application of Text Mining Methodology in the Identification of Plasticity of Concepts Contained in Large Sets of Scientific Publications, 2009)
The paper presents the application of text mining methodology in the identification of the concept plasticity in the field of information systems over the period of 30 years. A procedure that links the moving window technique with LSA algorithm (latent semantic analysis) [Deerwester et al. 1990] is proposed. Abstracts from all electronically available articles (2348), published in five renowned scientific journals of information systems domain: MIS Quarterly, Information Systems Research, Journal of Information Technology, Information Systems Journal and European Journal of Information Systems are used as a database for the research. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 240-247